2017
DOI: 10.1074/mcp.ra117.000082
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Signature Reveals Modulation of Human Macrophage Polarization and Functions Under Differing Environmental Oxygen Conditions

Abstract: Macrophages are innate immune cells which can react to a large number of environmental stimuli thanks to a high degree of plasticity. These cells are involved in a variety of tissue functions in homeostasis, and they play essential roles in pathological contexts. Macrophages' activation state, which determines their functional orientation, is strongly influenced by the cellular environment. A large body of macrophage literature is devoted to better defining polarizations from a molecular viewpoint. It is now a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 61 publications
4
32
0
Order By: Relevance
“…Hence, it is crucial to determine the most suitable differentiation conditions when using these cells as model system, as this can significantly impact their response to various innate immune stimuli. Quantitative high-resolution mass spectrometry-based proteomic approaches have been widely employed to investigate the proteomes of monocytes and macrophages as well as altered cellular proteomes and complex cellular/biological mechanisms in several biological conditions (21-23). However, to date, no studies have directly compared the proteome changes of the PMA-mediated differentiation process.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is crucial to determine the most suitable differentiation conditions when using these cells as model system, as this can significantly impact their response to various innate immune stimuli. Quantitative high-resolution mass spectrometry-based proteomic approaches have been widely employed to investigate the proteomes of monocytes and macrophages as well as altered cellular proteomes and complex cellular/biological mechanisms in several biological conditions (21-23). However, to date, no studies have directly compared the proteome changes of the PMA-mediated differentiation process.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotype plasticity of Mϕs is associated with a broad spectrum of activation states or polarizations, focusing on pro‐ and anti‐inflammatory states and classical (M1) versus alternative activation (M2a) . In this study, quantitative proteomics measured protein abundance profiles of 5,102 proteins from Mϕs at different polarization states mediated by high (18.6%) and low (3%) oxygen conditions . The results showed polarization‐specific markers (e.g., CD14, CD40, CD74, CD163, CD206, and CD274) and suggested an impact of oxygen on rates of phagocytosis of apoptotic cells.…”
Section: Quantitative Proteomic Profiling Of Innate Immune Cellsmentioning
confidence: 76%
“…To order to understand the involvement of TAM in chemoresistance in CRC, we designed the present study to incorporate oxygen concentration as a key environmental parameter. We had previously reported that the oxygen disponibility in macrophages' environment greatly influences their immune functions such as their ability to clear apoptotic cells (Court et al, 2017). As colon tissues are naturally exposed to levels of oxygen that are usually lower than 5% O2 (Keeley and Mann, 2018) with values that could reach even lower (<1% O2) in tumors, oxygen appeared as a fundamental parameter to understand macrophage involvement in chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TAMs increase hypoxia in tumor tissues, which is susceptible to favoring chemoresistance in return (Jeong et al, 2019). We also know that hypoxia affects macrophage biology (Court et al, 2017) and could mediate resistance to anticancer treatment and cancer relapse (Henze and Mazzone, 2016). Based on the abundance of macrophages in CRC, we hypothesized that hypoxia could directly modulate macrophage involvement in 5-FU resistance.…”
Section: Introductionmentioning
confidence: 99%